(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2022)
Macedonian proverbs and riddles which contain the city of Istanbul are excerpted from folk tales as cultural works and translated into Turkish. In addition, although in some of these proverbs the city of Istanbul is not mentioned at all, the name of the city of Istanbul is still present in the stories from which the proverbs are derived. The folk tales in which these proverbs were found, which are the subject of our research, have been translated into Turkish and are included in this paper. The purpose of this study is to understand the perception of the Macedonian people about the city of Istanbul through the mediation of Macedonian folk proverbs and riddles. Keywords: Istanbul; Macedonian proverbs; Macedonian riddles; Macedonian folklore.